Analisa Pengaruh Jumlah Pengoperasian CWP Terhadap Performa Kondensor PLTU Rembang - Andika Widya Pramono; Gita Puspa Artiani; Alan Laksono (JURNAL POWERPLANT, 2015)
Heat exchanger is a device used to transfer heat from one fluid to another fluid. One in Rembang heat exchanger is a condenser. The condenser serves to condense low pressure steam turbine output by using sea water as coolant fluid. The condenser is a turbine auxiliary equipment which, if having problems then it will result in generation efficiency. In the design of the contractor takes 4 CWP to supply cooling water condenser, but the reality on the ground, only 3 CWP operated. Therefore it is necessary to know how the effects of these operations on the performance of the condenser. The method of analysis is done by calculating the performance of the condenser is based on the current operating parameters of the performance test. By knowing the conditions and the actual performance of the condenser, it will be able to increase plant efficiency.